Illegitimate Recombination Between Homeologous Genes in Wheat Genome - Liu, Chao; Wang, Jinpeng; Sun, Pengchuan; Yu, Jigao; Meng, Fanbo; Zhang, Zhikang; Guo, He; Wei, Chendan; Li, Xinyu; Shen, Shaoqi; Wang, Xiyin (Frontiers in Plant Science, 2020)
Polyploidies produce a large number of duplicated regions and genes in genomes, which have a long-term impact and provide an important source of innovation for inheritance. High similarity between paralogous chromosomes, often divided into subgenomes, or paralogous regions after genome repatterning, may permit illegitimate DNA recombination or gene conversion. Here, based on gene colinearity, we aligned the (sub)genomes of common wheat (Triticum aestivum, AABBDD genotype) and its relatives, including Triticum urartu (AA), Aegilops tauschii (DD), and T. turgidum ssp. Dicoccoides (AABB) to detect the homologous genes within and between (sub)genomes. We also inferred more ancient paralogous regions. By comparing the sequence similarity between paralogous and orthologous genes, we inferred abnormality in topology of trees constructed, which could be explained by gene conversion a result of illegitimate recombination. Permeable numbers of inferred converted genes (>2000 gene pairs) suggested long-lasting genome instability of the hexaploid plant, and preferential donor roles by DD genes were found. Besides, though much restricted, duplicated genes produced millions of years ago also showed evidence of gene conversion. The present study will contribute to understanding the functional and structural innovation of the common wheat genome.